Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

Early olfactory, but not gustatory processing, is affected by the selection of heritable cognitive phenotypes in honey bee - Meghan M. Bennett; Chelsea N. Cook; Brian H. Smith; Hong Lei (Journal of Comparative Physiology A, 2021)